(untitled) (Indonesian Journal of Science and Technology, 2025)
Durian peels are biomass waste and can be used as an alternative fuel for briquettes. Therefore, processing organic waste (biomass), especially waste from durian peels into briquettes is a solution to replace traditional coal energy with renewable energy. This article contains guidelines that provide a basis for understanding how to make durian peel biomass briquettes and analyzing the results compared to coconut shell and rice husk materials. The test results showed that the highest density value was obtained for 100% rice husk briquettes with a value of 1324.56 kg/m3, the highest heating value was obtained for 100% coconut shell briquettes at 6479 kcal/kg, the voltage value produced by the voltaic cell Durian peel charcoal is highest when activated with more dilute KOH, in contrast to the durian peel charcoal electrolysis cell, the highest voltage is obtained when activated with more concentrated KOH.